Plan estratégico de marketing para incrementar las ventas en la florícola “Evergreen”, ubicada en la parroquia Aláquez. - Quimbita Velasco, Mery Geoconda (2022)
The strategic marketing plan is an essential tool that allows establishing steps to follow in terms of methodologies and times, to achieve certain objectives of a company successfully. The Evergreen flower company, is dedicated to the distribution and sale of flowers, currently its profitability has decreased due to increased competition. For this reason, it is intended to establish a new strategic marketing plan, to position the company within the market and improve its sales rate in the "Evergreen" floriculture, located in the Aláquez parish. Validation and exploratory factorial statistical analysis were applied, with a quantitative approach to determine the MAFE situational analysis for the development of a strategic marketing plan. In the results, it was observed the importance of each stage of the strategic marketing process and the development of some activities so that the company has a good business development centralized in the increase of sales and positioning within the market. Surveys were carried out on 32 potential clients of the company to obtain product, price, place and promotion strategies, company participation in international events and holidays, aspects of innovation and attraction of products to clients, pricing according to different aspects in times, competition and ease of acquisition for the client.